Metaphysical disputations, - Suárez, Francisco, 1548-1617 (Early modern Catholic sources ;, 2023)
"Francisco Suárez (1548-1617) was one of the most important philosophers and theologians of Early Modern Scholasticism. Although Suárez spent most of his academic career as a professor of theology, he is better known today for his Metaphysical Disputations (Salamanca, 1597). The present volume contains a facing-page English translation of Metaphysical Disputations III & IV. Metaphysical Disputation III offers a general treatment of the properties of being as such, while Metaphysical Disputation IV deals with one of these properties in particular, transcendental unity. The Latin text contained in this volume introduces a significant number of corrections to the text of the Vivès edition, the one standardly used by scholars of Suárez, and thus more faithfully reproduces the text of the first edition. The volume also contains a lengthy introduction that provides a detailed survey of the disputations' principal claims and arguments"--